High-entropy multiple silicon-carbon functional material and preparation method thereof, negative pole piece and lithium ion battery

By using high-entropy multi-silicon carbon functional materials in lithium-ion batteries, the thermal stability and structural reversibility of the positive electrode and negative electrode materials of lithium-ion batteries, as well as the volume expansion of the silicon negative electrode materials, are solved, and the energy density and electrochemical performance of the battery are improved.

CN119673993APending Publication Date: 2025-03-21AMPREUS WUXI CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411806471.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The positive and negative electrode materials of existing lithium-ion batteries have problems such as reduced thermal stability, flammability and explosion, poor structural reversibility, lattice oxygen loss and side reactions, especially after the increase of nickel elements and the increase of LCO charging cutoff voltage, the oxygen analysis and cation mixed discharge problems are caused. At the same time, the silicon negative electrode material will undergo volume expansion during the deintercalation of lithium, resulting in surface cracking and recombination of solid electrolyte membranes, consuming electrolyte solution, limiting its application.

Method used

Using high-entropy multi-silicon carbon functional materials, oxygen-rich high-entropy oxides are formed in situ on the multi-carbon gel support by microwave solubilizing the nano-silicon between the layers, and then coated with carbon gel to prepare high-entropy nanomaterials with ultra-small particle size to regulate the surface morphology and pore structure of the silicon carbon.

Benefits of technology

The energy density and electrochemical performance of lithium-ion batteries are improved, the structural stability of silicon carbon negative electrodes is optimized, the volume expansion and the recombination of solid electrolyte membranes are reduced, and the circulation efficiency and circulation stability of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673993A_ABST
    Figure CN119673993A_ABST
Patent Text Reader

Abstract

The invention discloses a high-entropy multiple silicon-carbon functional material and a preparation method thereof, a negative pole piece and a lithium ion battery. The high-entropy multiple silicon-carbon functional material is a composite negative pole material formed by compounding an oxygen-enriched high-entropy oxide, multiple carbon gel and nano silicon; in the high-entropy multiple silicon carbon functional material, the high-entropy oxide material is coated with multiple carbon gel to form a composite material, and the composite material is also loaded with nano silicon particles. The high-entropy multi-silicon-carbon functional material is applied to manufacturing of the lithium ion battery, and the high-entropy material has a specific multi-element synergistic effect, a large number of active sites and structural stability, so that the silicon-carbon negative electrode is further optimized, and the energy density and the electrochemical performance of a battery cell in the lithium ion battery can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a high-entropy multi-silicon-carbon functional material and a preparation method thereof, a negative electrode sheet and a lithium-ion battery. Background Art

[0002] In recent years, the growing demand for electric vehicles with long driving range and portable electronic devices with long driving time has accelerated the pace of developing lithium-ion batteries with high energy density. Among them, the positive and negative electrode materials are the active energy storage materials of lithium-ion batteries, and their selection determines the theoretical value of the energy density of lithium-ion batteries.

[0003] For example, in the positive electrode materials of lithium-ion batteries, the gram capacity can be improved by increasing the proportion of nickel in nickel, cobalt, manganese / aluminum, but the increase of nickel will cause the increase of residual alkali on the surface, the aggravation of cation mixing, the increase of strong oxidizing nickel, and the obvious oxygen precipitation phenomenon. In the battery, it is manifested as reduced thermal stability and flammability and explosion. Or increase the LCO charging cut-off voltage, however, the highly delithiated LCO faces many problems such as poor structural reversibility, lattice oxygen loss, side reactions and Co dissolution. Since the degree of delithiation on the LCO surface is higher than that in the bulk phase, the above problems are more likely to occur during the cycle.

[0004] In addition, the negative electrode also plays a vital role as a carrier for accepting lithium ions. Among the existing lithium storage negative electrode materials, silicon has an ultra-high theoretical specific capacity (4200mAh / g), as well as low discharge potential and environmental friendliness. However, silicon as a negative electrode material will produce a large volume expansion (>300%) during the process of lithium insertion and extraction, which will cause cracks on the silicon surface. The solid electrolyte (SEI) film will be re-formed at the cracks, consuming the electrolyte, causing its capacity to decay rapidly, limiting its application. Therefore, optimizing the deficiencies in the process of lithium insertion and extraction of silicon negative electrode materials is the focus of current research. To this end, researchers have done a lot of research on silicon-carbon negative electrode materials in recent years, mainly including: zero-dimensional-nanoparticles, one-dimensional-nanowires and nanotubes, two-dimensional-layered structures and three-dimensional-micron-scale spherical materials, but the fundamental problems that exist at present still have room for further improvement.

[0005] "High entropy" is a material design concept developed in recent years. It is a single-phase "multi-component" stable solid solution containing 5 or more elements. Its unique structural properties, chemical composition, and functional controllable characteristics have attracted widespread attention in the field of energy storage and conversion (especially in the application of electrochemical energy storage materials). By increasing the constituent elements to increase the entropy of the mixed configuration, the design space of electrochemical energy storage materials is broadened, bringing new opportunities for the development of current electrochemical energy storage materials. Summary of the invention

[0006] The purpose of the present invention is to provide a high-entropy multiple silicon-carbon functional material and a preparation method thereof, a negative electrode plate and a lithium-ion battery, and to obtain a high-entropy multiple silicon-carbon functional material by regulating the surface morphology and pore structure of silicon-carbon using high-entropy nanomaterials with ultra-small particle sizes, so as to prepare a high-performance lithium-ion battery.

[0007] To achieve the above purpose, the technical solution provided by the present invention is:

[0008] The first aspect of the present application provides a high-entropy multiple silicon-carbon functional material, which is a composite negative electrode material formed by a composite of oxygen-rich high-entropy oxide, multiple carbon gel and nano-silicon; in the high-entropy multiple silicon-carbon functional material, the high-entropy oxide material is coated by multiple carbon gel to form a composite material, and the composite material is also loaded with nano-silicon particles.

[0009] In order to optimize the above technical solutions, the specific limitations adopted also include:

[0010] The crystal structure of the oxygen-rich high-entropy oxide is one of a spinel structure, a perovskite structure, and a rock salt structure; the oxygen-rich high-entropy oxide contains at least five of the metal elements Cr, Ti, Mn, Fe, Co, Cu, Ni, Zn, Mg, Al, K, Li, Na, La, and Gd.

[0011] The particle size distribution of high entropy multiple silicon-carbon functional materials is 3 to 15 μm.

[0012] The second aspect of the present application provides a method for preparing a high entropy multi-silicon-carbon functional material, comprising the following steps:

[0013] preparing a metal salt solution;

[0014] Preparing graphite oxide dispersion;

[0015] The metal salt solution is mixed with the graphite oxide dispersion, and microwave heating is performed for in-situ reaction; freeze drying is performed to obtain a single-layer coated oxygen-rich high entropy oxide@carbon gel composite material;

[0016] Dispersing nano-silicon in a mixed solution of the metal salt solution and the graphite oxide dispersion to prepare a nano-silicon dispersion;

[0017] The surface of the single-coated oxygen-rich high-entropy oxide@carbon gel composite material is pierced, and nano-silicon dispersion is poured in, and microwave heating is performed for in-situ reaction; freeze drying is performed to obtain a double-coated oxygen-rich high-entropy oxide@carbon gel@silicon composite material;

[0018] Repeated puncture, injection of nano-silicon dispersion, microwave heating for in-situ reaction, and freeze-drying procedures to obtain a multi-coated oxygen-rich high-entropy oxide@carbon gel@silicon composite material;

[0019] The surface of the multi-coated oxygen-rich high entropy oxide@carbon gel@silicon composite material is punctured again, and a mixed solution formed by mixing a metal salt solution and a graphite oxide dispersion is poured into the surface, and microwave heating is performed for in-situ reaction; freeze drying is performed to obtain a high entropy multi-silicon-carbon functional material precursor;

[0020] The high entropy multiple silicon-carbon functional material precursor is sintered in an inert gas to obtain the high entropy multiple silicon-carbon functional material.

[0021] In order to optimize the above technical solutions, the specific limitations adopted also include:

[0022] The metal salt is a mixed metal salt containing at least five of the metal elements Cr, Ti, Mn, Fe, Co, Cu, Ni, Zn, Mg, Al, K, Li, Na, La, and Gd, and the molar ratio between the two metal elements is 1-4:1-4; the concentration of each metal element in the metal salt solution is 0.002-0.3 mol / L, and the stirring and dissolving time is 1-10 h; the metal salt is selected from nitrate, acetate, chloride, carbonate, oxalate or sulfate.

[0023] Furthermore, the graphite oxide dispersion is prepared by mixing the graphite oxide and the reducing agent, ultrasonically dispersing them in water, and heating them to react to form a mixed dispersion with viscosity; the reaction temperature is 50-100° C., and the mass ratio of the graphite oxide to the reducing agent is 1:1-3; after the graphite oxide and the reducing agent are mixed, the mass ratio of the mixed solid is 0.1%-20%, and the viscosity after heating is 2600-5000 Pa.s.

[0024] Furthermore, in each step of mixing the metal salt solution with the graphite oxide dispersion, the volume ratio of the metal salt solution to the graphite oxide dispersion is 1:1-10, and the stirring speed during mixing is between 0 and 1500 rpm.

[0025] Furthermore, in each step of the in-situ reaction by microwave heating, the reaction temperature is 110°C to 200°C, the heating rate is 5 to 30°C / min, and the reaction time is 2h to 20h.

[0026] Furthermore, in the nano-silicon dispersion, the nano-silicon content is 0.005-0.3 g / ml.

[0027] Repeat the processes of puncturing, injecting nano-silicon dispersion, microwave heating for in-situ reaction, and freeze drying at least three times to obtain a multi-coated oxygen-rich high entropy oxide@carbon gel@silicon composite material.

[0028] The sintering temperature is 300-700° C., the sintering time is 0.5-18 hours, and the obtained high-entropy multiple silicon-carbon functional material has a particle size distribution of 3-15 μm.

[0029] The third aspect of the present application provides a negative electrode plate, which contains the high-entropy multiple silicon-carbon functional material provided in the first aspect of the present application or the second aspect of the present application.

[0030] The fourth aspect of the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode plate provided in the third aspect of the present application.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The present invention uses high-entropy nanomaterials with ultra-small particle sizes to regulate the surface morphology and pore structure of silicon-carbon. The method is to form high-entropy oxides in situ on multiple carbon gel carriers by microwave solvothermal method, and load nano-silicon between its layers, and finally coat it with carbon gel to prepare high-entropy multiple silicon-carbon functional materials. The present invention applies high-entropy multiple silicon-carbon functional materials to the production of lithium-ion batteries. Since high-entropy materials have unique multi-element synergistic effects, a large number of active sites and structural stability, the silicon-carbon negative electrode is further optimized, which can significantly improve the energy density and electrochemical performance of the battery core in the lithium-ion battery, which is of great significance for the development of the next generation of high-energy lithium-ion power batteries.

[0033] Among them, the carbon carrier absorbs microwaves and converts them into high temperature. Its three-dimensional hierarchical structure and large specific surface area make the high entropy oxide precursor heated evenly and the particle size is uniform. The introduction of high entropy in functional materials effectively increases the concentration of oxygen vacancies. Its highly disordered atoms and lattice distortion effects form many internal defect structures, which accelerate the transfer of electrons and ions, thereby increasing the ion storage sites of the material. The thermodynamic high entropy effect enables the material to maintain a stable structure, which is beneficial to inhibiting the volume expansion of silicon. In addition, with the increase of the entropy value of the material, the positive electrode potential in the full battery with the addition of this material is reduced to a certain extent, which effectively improves the long-term cycle performance, especially for the high-voltage positive electrode.

[0034] The effects of various aspects of the present invention are specifically listed as follows:

[0035] 1. The thermodynamic high entropy effect, structural stability and multi-component synergistic effect of high entropy materials, as well as the repeated cycle process of carbon gelation similar to "weaving a net", make the carbon gel modified with high entropy materials have a strong and stable structure, which is beneficial to inhibit the volume expansion of silicon in the gel network and bring excellent cycle performance.

[0036] 2. The highly disordered and distorted lattice of high-entropy materials forms many internal defect structures. Vacancies are conducive to promoting the migration of electrons and ions, providing additional active sites for the reaction, thereby improving the electrochemical kinetic performance of the electrode.

[0037] 3. Apply high-entropy multiple silicon-carbon functional materials to lithium-ion batteries, and conduct three-electrode tests on the batteries. As the entropy value of the functional materials increases, the negative electrode voltage corresponding to the battery discharge end rises lower, and conversely, the positive electrode voltage corresponding to the battery charging end rises lower. That is, during the cycle, the negative electrode can achieve deep charging and shallow discharge, while the positive electrode is in a shallow charging and deep discharge state, thereby weakening the occurrence of SEI recombination caused by excessive delithiation of the negative electrode and structural collapse caused by excessive delithiation of the positive electrode, and the battery cycle coulombic efficiency and cycle stability are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a SEM image of the high entropy multiple silicon-carbon functional material in Example 1 of the present invention.

[0039] Figure 2 The EDS diagram showing different elements of the high entropy multiple silicon-carbon functional material in Example 1 of the present invention.

[0040] Figure 3 It is a comparison chart of intermittent high temperature cycle and expansion rate of the battery cells of Example 1 of the present invention and Comparative Example 1 at 45°C. DETAILED DESCRIPTION

[0041] The above contents of the present invention are further described in detail below in the form of embodiments, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies realized based on the above contents of the present invention belong to the scope of the present invention.

[0042] The experimental methods used in the following examples are all conventional methods unless otherwise specified, and the reagents, methods and equipment used are all conventional reagents, methods and equipment in the technical field unless otherwise specified.

[0043] For the sake of simplicity, this document only specifically discloses some numerical values ​​and optional ranges. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range. Similarly, any upper limit can be combined with any other upper limit to form an unambiguous range; the optional items in the optional range can also be combined arbitrarily.

[0044] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art.

[0045] The present application provides a high-entropy multiple silicon-carbon functional material, which is a composite negative electrode material formed by a composite of oxygen-rich high-entropy oxide, multiple carbon gel and nano-silicon; in the high-entropy multiple silicon-carbon functional material, the high-entropy oxide material is coated by the multiple carbon gel to form a composite material, and the composite material is also loaded with nano-silicon particles.

[0046] The crystal structure of the oxygen-rich high-entropy oxide is one of spinel structure, perovskite structure, and rock salt structure; the oxygen-rich high-entropy oxide contains at least five of the metal elements Cr, Ti, Mn, Fe, Co, Cu, Ni, Zn, Mg, Al, K, Li, Na, La, and Gd.

[0047] The particle size distribution of high entropy multiple silicon-carbon functional materials is 3 to 15 μm.

[0048] The present application also provides a method for preparing a high entropy multi-silicon-carbon functional material, comprising the following steps:

[0049] preparing a metal salt solution;

[0050] Preparing graphite oxide dispersion;

[0051] The metal salt solution is mixed with the graphite oxide dispersion, and microwave heating is performed for in-situ reaction; freeze drying is performed to obtain a single-layer coated oxygen-rich high entropy oxide@carbon gel composite material;

[0052] Dispersing nano-silicon in a mixture of a metal salt solution and a graphite oxide dispersion to prepare a nano-silicon dispersion;

[0053] The surface of the single-coated oxygen-rich high-entropy oxide@carbon gel composite material is pierced, and nano-silicon dispersion is poured in, and microwave heating is performed for in-situ reaction; freeze drying is performed to obtain a double-coated oxygen-rich high-entropy oxide@carbon gel@silicon composite material;

[0054] Repeated puncture, injection of nano-silicon dispersion, microwave heating for in-situ reaction, and freeze-drying procedures to obtain a multi-coated oxygen-rich high-entropy oxide@carbon gel@silicon composite material;

[0055] The surface of the multi-coated oxygen-rich high entropy oxide@carbon gel@silicon composite material is punctured again, and a mixed solution formed by mixing a metal salt solution and a graphite oxide dispersion is poured into the surface, and microwave heating is performed for in-situ reaction; freeze drying is performed to obtain a high entropy multi-silicon-carbon functional material precursor;

[0056] The high entropy multiple silicon-carbon functional material precursor is sintered in an inert gas to obtain the high entropy multiple silicon-carbon functional material.

[0057] In some embodiments, the method for preparing the metal salt solution is: mixing five or more elemental metal salts in a certain molar ratio, adding them to the polyol, and stirring until they are completely dissolved to form a mixed salt solution A.

[0058] Among them, the metal salt is a mixed metal salt containing at least five of the metal elements Cr, Ti, Mn, Fe, Co, Cu, Ni, Zn, Mg, Al, K, Li, Na, La, and Gd, and the molar ratio between the two metal elements is 1-4:1-4; the concentration of each metal element in the metal salt solution is 0.002-0.3 mol / L, and the stirring and dissolution time is 1-10h; the metal salt is selected from nitrate, acetate, chloride, carbonate, oxalate or sulfate.

[0059] In some embodiments, the method for preparing the graphite oxide dispersion is: mixing the graphite oxide and the reducing agent, ultrasonically dispersing them in deionized water, and heating them to react to form a mixed dispersion B with a certain viscosity.

[0060] The reaction temperature for heating the reaction to form a mixed dispersion with viscosity is 50-100°C, and the mass ratio of graphite oxide to reducing agent is 1:1-3; after the graphite oxide and the reducing agent are mixed, the mass ratio of the mixed solid is 0.1%-20%, and the viscosity after heating is 2600-5000 Pa.s.

[0061] In some embodiments, the metal salt solution is mixed with the graphite oxide dispersion, and the method for in-situ reaction by microwave heating is as follows: the dispersion B is continuously heated, and under stirring conditions, the salt solution A is quickly added to the dispersion B to form a mixed solution C, and after stirring for a certain period of time, the flocculent mixed solution C is added to a polytetrafluoroethylene reactor, and in a high-pressure closed environment, microwave heating is used for reaction, and no stirring is required during the reaction process, and an oxygen-rich high-entropy oxide@carbon hydrogel composite material is formed in situ.

[0062] In some embodiments, nano-silicon is dispersed in a mixed solution of a metal salt solution and a graphite oxide dispersion to prepare a nano-silicon dispersion by ultrasonically dispersing the nano-silicon in a mixed solution C to form a mixed solution D.

[0063] In each step of mixing the metal salt solution with the graphite oxide dispersion, the volume ratio of the metal salt solution to the graphite oxide dispersion is 1:1-10, and the stirring speed during mixing is between 0 and 1500 rpm.

[0064] In each step of the in-situ reaction by microwave heating, the reaction temperature is 110° C. to 200° C., the heating rate is 5 to 30° C. / min, and the reaction time is 2 h to 20 h.

[0065] In some embodiments, the nano-silicon content in the nano-silicon dispersion is 0.005-0.3 g / ml.

[0066] Repeat the processes of puncturing, injecting nano-silicon dispersion, microwave heating for in-situ reaction, and freeze drying at least three times to obtain a multi-coated oxygen-rich high entropy oxide@carbon gel@silicon composite material.

[0067] In some embodiments, the sintering temperature is 300-700° C. and the sintering time is 0.5-18 h, so that the particle size distribution of the obtained high entropy multiple silicon-carbon functional material is 3-15 μm.

[0068] The present application also provides a negative electrode plate, which contains the high-entropy multiple silicon-carbon functional material of the present application.

[0069] The present application also provides a lithium-ion battery, which contains the negative electrode plate of the present application.

[0070] In some embodiments, the lithium ion battery preparation steps are as follows:

[0071] S1 Preparation of positive electrode sheet: Mix the positive electrode active material, conductive agent, and binder dry powder and add them to a homogenizing tank for drying, then add the dispersion medium and continue stirring to obtain a viscous positive electrode slurry; or disperse the binder alone into the dispersion medium, mix well, and then mix and stir with the positive electrode active material and conductive agent to obtain a viscous positive electrode slurry; evenly coat the viscous positive electrode slurry on the aluminum foil current collector, dry, roll, cut, and weld the pole ears to prepare the positive electrode sheet;

[0072] S2 Preparation of negative electrode sheet: Mix the negative electrode active material, the high entropy multiple silicon-carbon functional material of the present application, the conductive agent, and the thickener dry powder, add them to a homogenizing tank, dry and evenly mix, then add the dispersion medium, continue stirring, and finally add the binder, stir evenly to obtain a viscous negative electrode slurry; or disperse the thickener separately into the dispersion medium, mix evenly, and then mix and stir with the negative electrode active material, the high entropy multiple silicon-carbon functional material, and the conductive agent, and finally add the binder, stir evenly to obtain a viscous negative electrode slurry; evenly apply the viscous negative electrode slurry on the copper foil collector, dry, roll, cut, and weld the pole ears to prepare the negative electrode sheet; in the negative electrode active material, the mass percentage of the high entropy multiple silicon-carbon functional material in the total dry powder slurry is ≥0wt%,

[0073] ≤60wt%;

[0074] S3 lithium-ion battery assembly: the positive electrode sheets and negative electrode sheets prepared in step S1 and step S2 are placed alternately with the separator to form an electrode group, which is loaded into a battery shell, packaged, injected, aged at high temperature, pressurized, and divided to prepare a lithium-ion battery;

[0075] Step S1: the positive electrode active material is one or a mixture of two or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium iron phosphate, and the dispersion medium is N-methyl pyrrolidone or deionized water.

[0076] In step S2, the negative electrode active material is one or a combination of two or more of natural graphite, artificial graphite, soft carbon, and hard carbon, and the dispersion medium is deionized water or N-methylpyrrolidone.

[0077] In an electrical device containing the battery of the present application, the battery can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, aircraft, ships and satellites, energy storage systems, electrical equipment, etc., but is not limited thereto; as an electrical device, the battery can be selected according to its usage requirements.

[0078] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments:

[0079] The following embodiments only list soft-package batteries, but are also applicable to batteries with other housings and structures, such as square steel shells, cylindrical batteries, etc.

[0080] The battery capacity designed in the following embodiments and comparative examples is 3Ah, the charge cut-off voltage is 4.5V, and the discharge cut-off voltage is 3.0V.

[0081] Example 1

[0082] 1. Dissolve ferric nitrate, cobalt nitrate, nickel nitrate, chromium nitrate and manganese nitrate in 100 mL of diethylene glycol at a metal element molar ratio of 1:1:1:1:1. The total concentration of the metal salts is 0.05 mol / L. Stir for 4 hours until completely dissolved to obtain a clear and transparent solution A.

[0083] 2. Mix 20g of graphite oxide and 25g of ascorbic acid, ultrasonically disperse them in 500g of deionized water, and heat them at 80°C to form a mixed dispersion B with a viscosity of about 2700mPa.s. At this time, continue to heat dispersion B, and quickly add salt solution A to dispersion B at a stirring speed of 800 rpm to form a mixed solution C; after stirring for a certain period of time, add the flocculent mixed solution C to a polytetrafluoroethylene reactor. In a high-pressure closed environment, the solvent thermal reaction heating rate is 15°C / min, the temperature is 170°C, and the reaction time is 5h. No further stirring is required during the reaction, and an oxygen-rich high-entropy oxide @ carbon hydrogel composite material is formed in situ. The hydrogel is placed in a freeze dryer for freeze drying to obtain a single-layer coated oxygen-rich high-entropy oxide @ carbon gel composite material.

[0084] 3. Puncture holes on the surface of the single-layer coated oxygen-rich high entropy oxide @ carbon gel, and then transfer it to a container. Ultrasonic disperse 12g of nanosilicon in the above mixed solution C to form a mixed solution D, pour the mixed solution D into the single-layer coated oxygen-rich high entropy oxide @ carbon gel with holes, and transfer it to a polytetrafluoroethylene reactor. In a high-pressure closed environment, the solvent thermal reaction temperature rise rate is 15℃ / min, the temperature is 170℃, and the reaction time is 4h. No stirring is required during the reaction process, and a double-layer coated oxygen-rich high entropy oxide @ carbon hydrogel @ silicon is formed in situ, which is also freeze-dried to obtain a double-layer coated oxygen-rich high entropy oxide @ carbon gel @ silicon composite material.

[0085] 4. Repeat step 3 for 4 times. For the last time, only the mixed solution D in step 3 is replaced with the mixed solution C in step 2. The rest is the same as step 3. At the same time, it is fully washed with deionized water before freeze-drying to obtain a high entropy multiple silicon-carbon functional material precursor.

[0086] 5. Place the high entropy multiple silicon-carbon functional material precursor prepared in step 4 in a tube furnace, and reduce it at 500°C for 2 hours in an Ar / H2 (volume ratio of 95:5) atmosphere to prepare a high entropy multiple silicon-carbon functional material.

[0087] 6. Preparation of positive electrode sheets: Mix the positive electrode active material lithium cobalt oxide, acetylene black, and binder PVDF dry powder in a mass ratio of 98.3:0.7:1, add them to a homogenization tank and dry them evenly, then add the dispersion medium NMP to make the solid content 72%-82%, continue stirring to obtain a viscous positive electrode slurry; evenly apply the viscous positive electrode slurry on the aluminum foil current collector, dry, roll, cut, and weld the pole ears to prepare the positive electrode sheets.

[0088] 7. Preparation of negative electrode sheet: Disperse the thickener CMC separately into the deionized water of the dispersion medium and stir evenly, add the negative electrode active material artificial graphite, high entropy multiple silicon-carbon functional materials, and acetylene black into the homogenization tank and dry evenly, then add the deionized water of the dispersion medium and the pre-dispersed CMC thickener in turn, adjust the solid content to 45%-55%, continue stirring, and finally add the binder SBR, stir evenly to obtain a viscous negative electrode slurry; wherein artificial graphite: high entropy multiple silicon-carbon functional materials: acetylene black: thickener CMC: binder SBR = 85:12:0.5:1:1.5. Finally, evenly coat the viscous negative electrode slurry on the copper foil current collector, dry, roll, cut, and weld the pole ears to prepare the negative electrode sheet.

[0089] 8. Lithium-ion battery assembly: The positive electrode sheet and negative electrode sheet prepared in step 6 and step 7 are wound together with the separator in a certain manner into an electrode group, loaded into a battery shell (formed by aluminum-plastic packaging film), packaged, injected, aged at high temperature, pressurized, and divided to prepare a lithium-ion battery.

[0090] Example 2

[0091] 1. Dissolve ferric nitrate, cobalt nitrate, nickel nitrate, chromium nitrate and manganese nitrate in 100 mL of diethylene glycol at a metal element molar ratio of 1:2:1:1:1. The total concentration of the metal salts is 0.1 mol / L. Stir for 6 hours until completely dissolved to obtain a clear and transparent solution A.

[0092] 2. Mix 20g of graphite oxide and 25g of ascorbic acid, ultrasonically disperse them in 500g of deionized water, and heat them at 80°C to form a mixed dispersion B with a viscosity of about 2800mPa.s. At this time, continue to heat dispersion B, and quickly add salt solution A to dispersion B at a stirring speed of 800 rpm to form a mixed solution C. After stirring for a certain period of time, add the flocculent mixed solution C to a polytetrafluoroethylene reactor. In a high-pressure closed environment, the solvent thermal reaction heating rate is 15°C / min, the temperature is 170°C, and the reaction time is 5h. No stirring is required during the reaction process, and an oxygen-rich high-entropy oxide @ carbon hydrogel composite material is formed in situ. The hydrogel is placed in a freeze dryer for freeze drying to obtain a single-layer coated oxygen-rich high-entropy oxide @ carbon gel composite material.

[0093] 3. Puncture holes on the surface of the single-layer coated oxygen-rich high entropy oxide @ carbon gel, and then transfer it to a container. Ultrasonic disperse 12g of nanosilicon in the above mixed solution C to form a mixed solution D, pour the mixed solution D into the single-layer coated oxygen-rich high entropy oxide @ carbon gel with holes, and transfer it to a polytetrafluoroethylene reactor. In a high-pressure closed environment, the solvent thermal reaction temperature rise rate is 15℃ / min, the temperature is 170℃, and the reaction time is 4h. No stirring is required during the reaction process, and a double-layer coated oxygen-rich high entropy oxide @ carbon hydrogel @ silicon is formed in situ, which is also freeze-dried to obtain a double-layer coated oxygen-rich high entropy oxide @ carbon gel @ silicon composite material.

[0094] 4. Repeat step 3 for 4 times. For the last time, only the mixed solution D in step 3 is replaced with the mixed solution C in step 2. The rest is the same as step 3. At the same time, it is fully washed with deionized water before freeze-drying to obtain a high entropy multiple silicon-carbon functional material precursor.

[0095] 5. Place the high entropy multiple silicon-carbon functional material precursor prepared in step 4 in a tube furnace, and reduce it at 500°C for 2 hours in an Ar / H2 (volume ratio of 95:5) atmosphere to prepare a high entropy multiple silicon-carbon functional material.

[0096] 6. Preparation of positive electrode sheets: Mix the positive electrode active material lithium cobalt oxide, acetylene black, and binder PVDF dry powder in a mass ratio of 98.3:0.7:1, add them to a homogenization tank and dry them evenly, then add the dispersion medium NMP to make the solid content 72%-82%, continue stirring to obtain a viscous positive electrode slurry; evenly apply the viscous positive electrode slurry on the aluminum foil current collector, dry, roll, cut, and weld the pole ears to prepare the positive electrode sheets.

[0097] 7. Preparation of negative electrode sheet: Disperse the thickener CMC separately into the deionized water of the dispersion medium and stir evenly, add the negative electrode active material artificial graphite, high entropy multiple silicon-carbon functional materials, and acetylene black into the homogenization tank and dry evenly, then add the deionized water of the dispersion medium and the pre-dispersed CMC thickener in turn, adjust the solid content to 45%-55%, continue stirring, and finally add the binder SBR, stir evenly to obtain a viscous negative electrode slurry; wherein artificial graphite: high entropy multiple silicon-carbon functional materials: acetylene black: thickener CMC: binder SBR = 85:12:0.5:1:1.5. Finally, evenly coat the viscous negative electrode slurry on the copper foil current collector, dry, roll, cut, and weld the pole ears to prepare the negative electrode sheet.

[0098] 8. Lithium-ion battery assembly: The positive electrode sheet and negative electrode sheet prepared in step 6 and step 7 are wound together with the separator in a certain manner into an electrode group, loaded into a battery shell (formed by aluminum-plastic packaging film), packaged, injected, aged at high temperature, pressurized, and divided to prepare a lithium-ion battery.

[0099] Example 3

[0100] 1. Dissolve ferric nitrate, cobalt nitrate, nickel nitrate, chromium nitrate and manganese nitrate in 100 mL of diethylene glycol at a metal element molar ratio of 1:1:1:1:1. The total concentration of the metal salts is 0.05 mol / L. Stir for 4 hours until completely dissolved to obtain a clear and transparent solution A.

[0101] 2. Mix 30g of graphite oxide and 35g of ascorbic acid, ultrasonically disperse them in 500g of deionized water, and heat them at 80°C to form a mixed dispersion B with a viscosity of about 3000mPa.s. At this time, continue to heat the dispersion B, and quickly add the salt solution A to the dispersion B at a stirring speed of 800 rpm to form a mixed solution C. After stirring for a certain period of time, add the flocculent mixed solution C to a polytetrafluoroethylene reactor. In a high-pressure closed environment, the solvent thermal reaction heating rate is 15°C / min, the temperature is 170°C, and the reaction time is 5h. No stirring is required during the reaction process, and an oxygen-rich high-entropy oxide @ carbon hydrogel composite material is formed in situ. The hydrogel is placed in a freeze dryer for freeze drying to obtain a single-layer coated oxygen-rich high-entropy oxide @ carbon gel composite material.

[0102] 3. Puncture holes on the surface of the single-layer coated oxygen-rich high entropy oxide @ carbon gel, and then transfer it to a container. Ultrasonic disperse 12g of nanosilicon in the above mixed solution C to form a mixed solution D, pour the mixed solution D into the single-layer coated oxygen-rich high entropy oxide @ carbon gel with holes, and transfer it to a polytetrafluoroethylene reactor. In a high-pressure closed environment, the solvent thermal reaction temperature rise rate is 15℃ / min, the temperature is 170℃, and the reaction time is 4h. No stirring is required during the reaction process, and a double-layer coated oxygen-rich high entropy oxide @ carbon hydrogel @ silicon is formed in situ, which is also freeze-dried to obtain a double-layer coated oxygen-rich high entropy oxide @ carbon gel @ silicon composite material.

[0103] 4. Repeat step 3 for 4 times. For the last time, only the mixed solution D in step 3 is replaced with the mixed solution C in step 2. The rest is the same as step 3. At the same time, it is fully washed with deionized water before freeze-drying to obtain a high entropy multiple silicon-carbon functional material precursor.

[0104] 5. Place the high entropy multiple silicon-carbon functional material precursor prepared in step 4 in a tube furnace, and reduce it at 600°C for 2 hours in an Ar / H2 (volume ratio of 95:5) atmosphere to prepare a high entropy multiple silicon-carbon functional material.

[0105] 6. Preparation of positive electrode sheets: Mix the positive electrode active material lithium cobalt oxide, acetylene black, and binder PVDF dry powder in a mass ratio of 98.3:0.7:1, add them to a homogenization tank and dry them evenly, then add the dispersion medium NMP to make the solid content 72%-82%, continue stirring to obtain a viscous positive electrode slurry; evenly apply the viscous positive electrode slurry on the aluminum foil current collector, dry, roll, cut, and weld the pole ears to prepare the positive electrode sheets.

[0106] 7. Preparation of negative electrode sheet: Disperse the thickener CMC separately into the deionized water of the dispersion medium and stir evenly, add the negative electrode active material artificial graphite, high entropy multiple silicon-carbon functional materials, and acetylene black into the homogenization tank and dry evenly, then add the deionized water of the dispersion medium and the pre-dispersed CMC thickener in turn, adjust the solid content to 45%-55%, continue stirring, and finally add the binder SBR, stir evenly to obtain a viscous negative electrode slurry; wherein artificial graphite: high entropy multiple silicon-carbon functional materials: acetylene black: thickener CMC: binder SBR = 85:12:0.5:1:1.5. Finally, evenly coat the viscous negative electrode slurry on the copper foil current collector, dry, roll, cut, and weld the pole ears to prepare the negative electrode sheet.

[0107] 8. Lithium-ion battery assembly: The positive electrode sheet and negative electrode sheet prepared in step 6 and step 7 are wound together with the separator in a certain manner into an electrode group, loaded into a battery shell (formed by aluminum-plastic packaging film), packaged, injected, aged at high temperature, pressurized, and divided to prepare a lithium-ion battery.

[0108] Example 4

[0109] 1. Dissolve ferric nitrate, cobalt nitrate, nickel nitrate, chromium nitrate and manganese nitrate in 100 mL of diethylene glycol at a metal element molar ratio of 1:1:1:1:1. The total concentration of the metal salts is 0.05 mol / L. Stir for 4 hours until completely dissolved to obtain a clear and transparent solution A.

[0110] 2. Mix 30g of graphite oxide and 35g of ascorbic acid, ultrasonically disperse them in 500g of deionized water, and heat them at 80°C to form a mixed dispersion B with a viscosity of about 3500mPa.s. At this time, continue to heat dispersion B, and quickly add salt solution A to dispersion B at a stirring speed of 800 rpm to form a mixed solution C. After stirring for a certain period of time, add the flocculent mixed solution C to a polytetrafluoroethylene reactor. In a high-pressure closed environment, the solvent thermal reaction heating rate is 15°C / min, the temperature is 170°C, and the reaction time is 5h. No stirring is required during the reaction process, and an oxygen-rich high-entropy oxide @ carbon hydrogel composite material is formed in situ. The hydrogel is placed in a freeze dryer for freeze drying to obtain a single-layer coated oxygen-rich high-entropy oxide @ carbon gel composite material.

[0111] 3. Puncture holes on the surface of the single-layer coated oxygen-rich high entropy oxide @ carbon gel, and then transfer it to a container. Ultrasonic disperse 20g of nano-silicon in the above mixed solution C to form a mixed solution D, pour the mixed solution D into the single-layer coated oxygen-rich high entropy oxide @ carbon gel with holes, and transfer it to a polytetrafluoroethylene reactor. In a high-pressure closed environment, the solvent thermal reaction temperature rise rate is 15℃ / min, the temperature is 170℃, and the reaction time is 4h. No stirring is required during the reaction process, and a double-layer coated oxygen-rich high entropy oxide @ carbon hydrogel @ silicon is formed in situ, which is also freeze-dried to obtain a double-layer coated oxygen-rich high entropy oxide @ carbon gel @ silicon composite material.

[0112] 4. Repeat step 3 for a total of 5 times. For the last time, only the mixed solution D in step 3 is replaced with the mixed solution C in step 2. The rest is the same as step 3. At the same time, it is fully washed with deionized water before freeze-drying to obtain a high entropy multiple silicon-carbon functional material precursor.

[0113] 5. Place the high entropy multiple silicon-carbon functional material precursor prepared in step 4 in a tube furnace, and reduce it at 500°C for 2 hours in an Ar / H2 (volume ratio of 95:5) atmosphere to prepare a high entropy multiple silicon-carbon functional material.

[0114] 6. Preparation of positive electrode sheets: Mix the positive electrode active material lithium cobalt oxide, acetylene black, and binder PVDF dry powder in a mass ratio of 98.3:0.7:1, add them to a homogenization tank and dry them evenly, then add the dispersion medium NMP to make the solid content 72%-82%, continue stirring to obtain a viscous positive electrode slurry; evenly apply the viscous positive electrode slurry on the aluminum foil current collector, dry, roll, cut, and weld the pole ears to prepare the positive electrode sheets.

[0115] 7. Preparation of negative electrode sheet: Disperse the thickener CMC separately into the deionized water of the dispersion medium and stir evenly, add the negative electrode active material artificial graphite, high entropy multiple silicon-carbon functional materials, and acetylene black into the homogenization tank and dry evenly, then add the deionized water of the dispersion medium and the pre-dispersed CMC thickener in turn, adjust the solid content to 45%-55%, continue stirring, and finally add the binder SBR, stir evenly to obtain a viscous negative electrode slurry; wherein artificial graphite: high entropy multiple silicon-carbon functional materials: acetylene black: thickener CMC: binder SBR = 85:12:0.5:1:1.5. Finally, evenly coat the viscous negative electrode slurry on the copper foil current collector, dry, roll, cut, and weld the pole ears to prepare the negative electrode sheet.

[0116] 8. Lithium-ion battery assembly: The positive electrode sheet and negative electrode sheet prepared in step 6 and step 7 are wound together with the separator in a certain manner into an electrode group, loaded into a battery shell (formed by aluminum-plastic packaging film), packaged, injected, aged at high temperature, pressurized, and divided to prepare a lithium-ion battery.

[0117] Example 5

[0118] 1. Dissolve ferric nitrate, cobalt nitrate, nickel nitrate, copper nitrate and zinc nitrate in 100 mL of diethylene glycol at a metal element molar ratio of 1:1:1:1:1. The total concentration of the metal salts is 0.05 mol / L. Stir for 4 hours until completely dissolved to obtain a clear and transparent solution A.

[0119] 2. Mix 20g of graphite oxide and 25g of ascorbic acid, ultrasonically disperse them in 500g of deionized water, and heat them at 80°C to form a mixed dispersion B with a viscosity of about 3500mPa.s. At this time, continue to heat dispersion B, and quickly add salt solution A to dispersion B at a stirring speed of 800 rpm to form a mixed solution C. After stirring for a certain period of time, add the flocculent mixed solution C to a polytetrafluoroethylene reactor. In a high-pressure closed environment, the solvent thermal reaction heating rate is 15°C / min, the temperature is 170°C, and the reaction time is 5h. No stirring is required during the reaction process, and an oxygen-rich high-entropy oxide @ carbon hydrogel composite material is formed in situ. The hydrogel is placed in a freeze dryer for freeze drying to obtain a single-layer coated oxygen-rich high-entropy oxide @ carbon gel composite material.

[0120] 3. Puncture holes on the surface of the single-layer coated oxygen-rich high entropy oxide @ carbon gel, and then transfer it to a container. Ultrasonic disperse 12g of nanosilicon in the above mixed solution C to form a mixed solution D, pour the mixed solution D into the single-layer coated oxygen-rich high entropy oxide @ carbon gel with holes, and transfer it to a polytetrafluoroethylene reactor. In a high-pressure closed environment, the solvent thermal reaction temperature rise rate is 15℃ / min, the temperature is 170℃, and the reaction time is 4h. No stirring is required during the reaction process, and a double-layer coated oxygen-rich high entropy oxide @ carbon hydrogel @ silicon is formed in situ, which is also freeze-dried to obtain a double-layer coated oxygen-rich high entropy oxide @ carbon gel @ silicon composite material.

[0121] 4. Repeat step 3 for 4 times. For the last time, only the mixed solution D in step 3 is replaced with the mixed solution C in step 2. The rest is the same as step 3. At the same time, it is fully washed with deionized water before freeze-drying to obtain a high entropy multiple silicon-carbon functional material precursor.

[0122] 5. Place the high entropy multiple silicon-carbon functional material precursor prepared in step 4 in a tube furnace, and reduce it at 600°C for 3 hours in an Ar / H2 (volume ratio of 95:5) atmosphere to prepare a high entropy multiple silicon-carbon functional material.

[0123] 6. Preparation of positive electrode sheets: Mix the positive electrode active material lithium cobalt oxide, acetylene black, and binder PVDF dry powder in a mass ratio of 98.3:0.7:1, add them to a homogenization tank and dry them evenly, then add the dispersion medium NMP to make the solid content 72%-82%, continue stirring to obtain a viscous positive electrode slurry; evenly apply the viscous positive electrode slurry on the aluminum foil current collector, dry, roll, cut, and weld the pole ears to prepare the positive electrode sheets.

[0124] 7. Preparation of negative electrode sheet: Disperse the thickener CMC separately into the deionized water of the dispersion medium and stir evenly, add the negative electrode active material artificial graphite, high entropy multiple silicon-carbon functional materials, and acetylene black into the homogenization tank and dry evenly, then add the deionized water of the dispersion medium and the pre-dispersed CMC thickener in turn, adjust the solid content to 45%-55%, continue stirring, and finally add the binder SBR, stir evenly to obtain a viscous negative electrode slurry; wherein artificial graphite: high entropy multiple silicon-carbon functional materials: acetylene black: thickener CMC: binder SBR = 85:12:0.5:1:1.5. Finally, evenly coat the viscous negative electrode slurry on the copper foil current collector, dry, roll, cut, and weld the pole ears to prepare the negative electrode sheet.

[0125] 8. Lithium-ion battery assembly: The positive electrode sheet and negative electrode sheet prepared in step 6 and step 7 are wound together with the separator in a certain manner into an electrode group, loaded into a battery shell (formed by aluminum-plastic packaging film), packaged, injected, aged at high temperature, pressurized, and divided to prepare a lithium-ion battery.

[0126] Example 6

[0127] 1. Dissolve ferric nitrate, cobalt nitrate, nickel nitrate, chromium nitrate and manganese nitrate in 100 mL of diethylene glycol at a metal element molar ratio of 1:1:1:1:1. The total concentration of the metal salts is 0.05 mol / L. Stir for 4 hours until completely dissolved to obtain a clear and transparent solution A.

[0128] 2. Mix 30g of graphite oxide and 35g of ascorbic acid, ultrasonically disperse them in 700g of deionized water, and heat them at 70°C to form a mixed dispersion B with a viscosity of about 3000mPa.s. At this time, continue to heat the dispersion B, and quickly add the salt solution A to the dispersion B at a stirring speed of 800 rpm to form a mixed solution C. After stirring for a certain period of time, add the flocculent mixed solution C to a polytetrafluoroethylene reactor. In a high-pressure closed environment, the solvent thermal reaction heating rate is 15°C / min, the temperature is 170°C, and the reaction time is 5h. No stirring is required during the reaction process, and an oxygen-rich high entropy oxide @ carbon hydrogel composite material is formed in situ. The hydrogel is placed in a freeze dryer for freeze drying to obtain a single-layer coated oxygen-rich high entropy oxide @ carbon gel composite material.

[0129] 3. Puncture holes on the surface of the single-layer coated oxygen-rich high entropy oxide @ carbon gel, and then transfer it to a container. Ultrasonic disperse 12g of nanosilicon in the above mixed solution C to form a mixed solution D, pour the mixed solution D into the single-layer coated oxygen-rich high entropy oxide @ carbon gel with holes, and transfer it to a polytetrafluoroethylene reactor. In a high-pressure closed environment, the solvent thermal reaction temperature rise rate is 15℃ / min, the temperature is 170℃, and the reaction time is 4h. No stirring is required during the reaction process, and a double-layer coated oxygen-rich high entropy oxide @ carbon hydrogel @ silicon is formed in situ, which is also freeze-dried to obtain a double-layer coated oxygen-rich high entropy oxide @ carbon gel @ silicon composite material.

[0130] 4. Repeat step 3 for 4 times. For the last time, only the mixed solution D in step 3 is replaced with the mixed solution C in step 2. The rest is the same as step 3. At the same time, it is fully washed with deionized water before freeze-drying to obtain a high entropy multiple silicon-carbon functional material precursor.

[0131] 5. Place the high entropy multiple silicon-carbon functional material precursor prepared in step 4 in a tube furnace, and reduce it at 600°C for 3 hours in an Ar / H2 (volume ratio of 95:5) atmosphere to prepare a high entropy multiple silicon-carbon functional material.

[0132] 6. Preparation of positive electrode sheets: Mix the positive electrode active material lithium cobalt oxide, acetylene black, and binder PVDF dry powder in a mass ratio of 98.3:0.7:1, add them to a homogenization tank and dry them evenly, then add the dispersion medium NMP to make the solid content 72%-82%, continue stirring to obtain a viscous positive electrode slurry; evenly apply the viscous positive electrode slurry on the aluminum foil current collector, dry, roll, cut, and weld the pole ears to prepare the positive electrode sheets.

[0133] 7. Preparation of negative electrode sheet: Disperse the thickener CMC separately into the deionized water of the dispersion medium and stir evenly, add the negative electrode active material artificial graphite, high entropy multiple silicon-carbon functional materials, and acetylene black into the homogenization tank and dry evenly, then add the deionized water of the dispersion medium and the pre-dispersed CMC thickener in turn, adjust the solid content to 45%-55%, continue stirring, and finally add the binder SBR, stir evenly to obtain a viscous negative electrode slurry; wherein artificial graphite: high entropy multiple silicon-carbon functional materials: acetylene black: thickener CMC: binder SBR = 85:12:0.5:1:1.5. Finally, evenly coat the viscous negative electrode slurry on the copper foil current collector, dry, roll, cut, and weld the pole ears to prepare the negative electrode sheet.

[0134] 8. Lithium-ion battery assembly: The positive electrode sheet and negative electrode sheet prepared in step 6 and step 7 are wound together with the separator in a certain manner into an electrode group, loaded into a battery shell (formed by aluminum-plastic packaging film), packaged, injected, aged at high temperature, pressurized, and divided to prepare a lithium-ion battery.

[0135] Comparative Example 1

[0136] The battery design process, raw materials, and production steps adopted in Comparative Example 1 are basically the same as those in Example 1. The only difference is that the negative electrode slurry in Comparative Example 1 does not use the high-entropy multiple silicon-carbon functional material prepared by the present invention, but a conventional silicon-carbon material on the market.

[0137] Comparative Example 2

[0138] The scheme of Comparative Example 2 is basically the same as that of Example 1, except that there is no configuration of the metal salt solution, and the step 1 of "dissolving ferric nitrate, cobalt nitrate, nickel nitrate, chromium nitrate, and manganese nitrate in a metal element molar ratio of 1:1:1:1:1 in 100 mL of diethylene glycol, with a total concentration of metal salts of 0.05 mol / L, and stirring for 4 hours until completely dissolved to obtain a clear and transparent solution A" is replaced by "using 100 mL of diethylene glycol directly as solution A".

[0139] The test showed that the composite material of Comparative Example 2 had poor performance due to the lack of modification of high entropy materials.

[0140] Comparative Example 3

[0141] Comparative Example 3 is substantially the same as Example 1, except that in step 2, the viscosity of the mixed dispersion B formed by the heating reaction is 5400 mPa.s.

[0142] Comparative Example 4

[0143] Comparative Example 4 is substantially the same as Example 1, except that in step 2, the viscosity of the mixed dispersion B formed by the heating reaction is 500 mPa.s.

[0144] The test showed that too high or too low viscosity of the mixed dispersion B can easily lead to uneven in-situ formation of high entropy materials on the carbon gel carrier. Too high or too low viscosity can also lead to incomplete encapsulation of nano-silicon. The failure of silicon to be effectively encapsulated will significantly affect battery performance.

[0145] The viscosity of the mixed dispersion B is preferably between 2600 and 5000 Pa.s.

[0146] Table 1 is a comparison of the 3C rate discharge capacity percentage and the capacity retention rate after normal temperature and high temperature cycles of the battery cells prepared in Examples 1 to 6 of the present invention and Comparative Examples 1 to 4.

[0147] Table 1 3C rate discharge capacity percentage and capacity retention parameters after normal temperature and high temperature cycles of batteries prepared in various embodiments and comparative examples

[0148]

[0149] It can be seen from the data in Table 1 that the high energy density battery designed using the high entropy multiple silicon-carbon functional materials prepared by the present invention has good rate discharge performance, with a capacity percentage of about 3% or more improvement at 3C rate discharge capacity / 0.2C rate discharge capacity. In addition, regardless of room temperature or high temperature, the long-term cycle life is significantly improved, and the capacity retention rate of the embodiment at 25 degrees is improved by >1% compared with the control example with the same number of cycles, and at 45 degrees, it is improved by >3%. The excellent rate performance is mainly due to the good electrochemical kinetics of the high entropy multiple silicon-carbon functional materials, and the improvement in cycle performance is mainly attributed to the fact that the high entropy multiple silicon-carbon functional materials have a strong and stable structure, which reduces the loss of active lithium caused by the frequent repair of SEI during the cycle.

[0150] Table 2 is a comparison of the high temperature storage performance of the battery cells of Examples 1 to 6 of the present invention and Comparative Examples 1 to 4 at 60°C / 85°C.

[0151] Table 2 Thickness growth rate, residual capacity and recovery capacity percentage parameters of batteries prepared in various embodiments and comparative examples after 60°C / 85°C high temperature storage

[0152]

[0153] From the data in Table 2, it can be seen that the high energy density battery designed with the high entropy multiple silicon-carbon functional materials prepared by the present invention has good high temperature storage performance. Regardless of whether it is stored at 60°C for 30 days or 85°C for 18 hours, the embodiment has a more obvious residual and recovery capacity advantage than the comparative example, which shows that at high temperature, the internal system of the battery of the embodiment is more stable. This is mainly due to the thermodynamic high entropy effect, structural stability and multi-component synergistic effect of the high entropy material, which makes the carbon gel modified with the high entropy material have a strong and stable structure.

[0154] Figure 1 , Figure 2 They are respectively the SEM and EDS images of the high entropy multiple silicon-carbon functional material in Example 1 of the present invention. The SEM image shows carbon-wrapped silicon nanoparticles; the EDS element distribution diagram is mainly C and Si elements, and in addition, a small amount of elements in the high entropy material are evenly distributed, indicating that the present invention has successfully synthesized a high entropy multiple silicon-carbon functional material.

[0155] Figure 3 The intermittent high-temperature cycle and expansion rate of the battery cells of Example 1 of the present invention and Comparative Example 1 at 45°C are compared; the upper row is the three repeated test measurements of Example 1, and the lower row is the three repeated test measurements of Comparative Example 1. Compared with the conventional cycle system, the intermittent cycle system has an additional step of fully charged and placed for 24 hours. The long-term high-temperature placement at full charge puts high demands on the high-temperature cycle and high-temperature storage performance of the battery. It can be seen that the battery designed with the high-entropy multiple silicon-carbon functional materials prepared by the present invention exhibits a very excellent cycle life. With the same capacity retention rate, the cycle of Example 1 is nearly 20 more than that of the comparative example. In addition, the expansion rate of the initial half-electric thickness after full charge every 10 cycles is 1% higher than that of Example 1. The excellent cycle performance and expansion rate are mainly attributed to the application of high-entropy multiple silicon-carbon functional materials, which enables the negative electrode to achieve deep charge and shallow discharge during the cycle, and the positive electrode is in a shallow charge and deep discharge state, thereby weakening the occurrence of SEI recombination caused by excessive delithiation of the negative electrode and structural collapse caused by excessive delithiation of the positive electrode.

[0156] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, according to the technical essence of the present invention, any simple modification, equivalent replacement and improvement made to the above embodiment still falls within the protection scope of the technical solution of the present invention.

Claims

1. A high entropy multi-silicon-carbon functional material, characterized in that: The high-entropy multiple silicon-carbon functional material is a composite negative electrode material formed by a composite of oxygen-rich high-entropy oxide, multiple carbon gel and nano-silicon; in the high-entropy multiple silicon-carbon functional material, the high-entropy oxide material is coated by multiple carbon gel to form a composite material, and the composite material is also loaded with nano-silicon particles.

2. The high entropy multi-silicon-carbon functional material according to claim 1, characterized in that: The crystal structure of the oxygen-rich high-entropy oxide is one of a spinel structure, a perovskite structure, and a rock salt structure; the oxygen-rich high-entropy oxide contains at least five of the metal elements Cr, Ti, Mn, Fe, Co, Cu, Ni, Zn, Mg, Al, K, Li, Na, La, and Gd.

3. The high entropy multi-silicon-carbon functional material according to claim 1, characterized in that: The particle size distribution of high entropy multiple silicon-carbon functional materials is 3 to 15 μm.

4. A method for preparing a high entropy multi-silicon-carbon functional material, characterized in that: The following steps are involved: preparing a metal salt solution; Preparing graphite oxide dispersion; The metal salt solution is mixed with the graphite oxide dispersion, and microwave heating is performed for in-situ reaction; freeze drying is performed to obtain a single-layer coated oxygen-rich high entropy oxide@carbon gel composite material; Dispersing nano-silicon in a mixture of a metal salt solution and a graphite oxide dispersion to prepare a nano-silicon dispersion; The surface of the single-coated oxygen-rich high-entropy oxide@carbon gel composite material is pierced, and nano-silicon dispersion is poured in, and microwave heating is performed for in-situ reaction; freeze drying is performed to obtain a double-coated oxygen-rich high-entropy oxide@carbon gel@silicon composite material; Repeated puncture, injection of nano-silicon dispersion, microwave heating for in-situ reaction, and freeze-drying procedures to obtain a multi-coated oxygen-rich high-entropy oxide@carbon gel@silicon composite material; The surface of the multi-coated oxygen-rich high entropy oxide@carbon gel@silicon composite material is punctured again, and a mixed solution formed by mixing a metal salt solution and a graphite oxide dispersion is poured into the surface, and microwave heating is performed for in-situ reaction; freeze drying is performed to obtain a high entropy multi-silicon-carbon functional material precursor; The high entropy multiple silicon-carbon functional material precursor is sintered in an inert gas to obtain the high entropy multiple silicon-carbon functional material.

5. The method for preparing high entropy multiple silicon-carbon functional materials according to claim 4, characterized in that: The metal salt is a mixed metal salt containing at least five of the metal elements Cr, Ti, Mn, Fe, Co, Cu, Ni, Zn, Mg, Al, K, Li, Na, La, and Gd, and the molar ratio between the two metal elements is 1-4:1-4; the concentration of each metal element in the metal salt solution is 0.002-0.3 mol / L, and the stirring and dissolving time is 1-10 h; the metal salt is selected from nitrate, acetate, chloride, carbonate, oxalate or sulfate.

6. The method for preparing a high entropy multi-silicon-carbon functional material according to claim 4, characterized in that: The graphite oxide dispersion is prepared by mixing the graphite oxide and a reducing agent, ultrasonically dispersing them in water, and heating them to react to form a mixed dispersion with viscosity; the reaction temperature is 50-100°C, and the mass ratio of the graphite oxide to the reducing agent is 1:1-3; after the graphite oxide and the reducing agent are mixed, the mass ratio of the mixed solid is 0.1%-20%, and the viscosity after heating is 2600-5000 Pa.s.

7. The method for preparing a high entropy multiple silicon-carbon functional material according to claim 4, characterized in that: In each step of mixing the metal salt solution and the graphite oxide dispersion, the volume ratio of the metal salt solution to the graphite oxide dispersion is 1:1-10, and the stirring speed during mixing is between 0 and 1500 rpm.

8. The method for preparing high entropy multiple silicon-carbon functional materials according to claim 4, characterized in that: In each step of the in-situ reaction by microwave heating, the reaction temperature is 110° C. to 200° C., the heating rate is 5 to 30° C. / min, and the reaction time is 2 h to 20 h.

9. The method for preparing a high entropy multi-silicon-carbon functional material according to claim 4, characterized in that: The nano silicon content in the nano silicon dispersion is 0.005-0.3 g / ml.

10. The method for preparing high entropy multiple silicon-carbon functional materials according to claim 4, characterized in that: The process including puncturing, injecting nano-silicon dispersion, microwave heating for in-situ reaction, and freeze drying is repeated at least three times to obtain a multi-coated oxygen-rich high entropy oxide@carbon gel@silicon composite material.

11. The method for preparing a high entropy multiple silicon-carbon functional material according to claim 4, characterized in that: The sintering temperature is 300-700°C, and the sintering time is 0.5-18h.

12. A negative electrode plate, characterized in that: The negative electrode plate contains a high-entropy multi-silicon-carbon functional material prepared by the method described in any one of claims 1-3 or any one of claims 4-11.

13. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet according to claim 12.

Citation Information

Cited By

  • Catalytic filler, preparation method and application of catalytic filler in treatment of organic matters in high-salinity wastewater by electrochemistry and ozone

    CN121669267A

  • Catalytic filler, preparation method and application thereof in electrochemical synergistic ozone treatment of high-salinity wastewater

    CN121669267B